2006
DOI: 10.1038/sj.mp.4001812
|View full text |Cite
|
Sign up to set email alerts
|

Association between the arginine vasopressin 1a receptor (AVPR1a) gene and autism in a family-based study: mediation by socialization skills

Abstract: We examined three microsatellites in the arginine vasopressin 1a receptor gene (AVPR1a), two in the promoter region (RS1 and RS3) and an intronic microsatellite (AVR), for association with autism as well as scores on the Vineland Adaptive Behavior Scale (VABS), the Autism Diagnostic Interview-Revised (ADI-R) and the Autism Diagnostic Observation Scale-Generic (ADOS-G), measures that are widely used to diagnose autism spectrum disorders. We tested for association between the AVPR1a microsatellites and autism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
138
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(149 citation statements)
references
References 19 publications
9
138
0
2
Order By: Relevance
“…Additionally, SNPs associated with ASD are also associated with amygdala volume [29], depression/anxiety [29], negative emotionality [30], attention deficit [31], adult attachment styles [32,33] (but see [34]), affectivity, emotional loneliness and IQ [35], empathy and stress reactivity [36], observed parenting [37], with sexual phenotypes [38] and in our own studies with prosocial behavior [39]. Interestingly, the AVPR1a receptor of the closely related nonapeptide vasopressin has also been associated with ASD [40][41][42]. This provisional role of OT in ASD, is further supported by two linkage studies [43,44], clinical evidence by several groups demonstrating clinical improvement in ASD following OT administration [45][46][47][48][49][50][51] (also see [52,53]) and studies showing that ASD is also associated with alterations in OT plasma levels [54].…”
Section: Oxytocin and Autism Spectrum Disorders (Asd)mentioning
confidence: 59%
“…Additionally, SNPs associated with ASD are also associated with amygdala volume [29], depression/anxiety [29], negative emotionality [30], attention deficit [31], adult attachment styles [32,33] (but see [34]), affectivity, emotional loneliness and IQ [35], empathy and stress reactivity [36], observed parenting [37], with sexual phenotypes [38] and in our own studies with prosocial behavior [39]. Interestingly, the AVPR1a receptor of the closely related nonapeptide vasopressin has also been associated with ASD [40][41][42]. This provisional role of OT in ASD, is further supported by two linkage studies [43,44], clinical evidence by several groups demonstrating clinical improvement in ASD following OT administration [45][46][47][48][49][50][51] (also see [52,53]) and studies showing that ASD is also associated with alterations in OT plasma levels [54].…”
Section: Oxytocin and Autism Spectrum Disorders (Asd)mentioning
confidence: 59%
“…These findings contribute to an ongoing debate (58) that, on one hand, questions the value of reducing complex multidimentional disorders such as ASD to a single diagnosis, although its degree of inclusivity can vary, and, on the other hand, brings up issues such as measurement noise and higher rates of Type II error characteristic of componential, facet-based approaches to complex conditions. In addition, our findings, especially those pertaining to associations with DβH, contribute to the literature on the importance of including the Vineland in studies of etiology of ASD (59).…”
Section: Discussionmentioning
confidence: 89%
“…Wassink et al 6 found significant disequilibrium with both RS1 and RS3 but only in cases without language deficits. In this new paper, Yirmiya et al 7 fail to find the association with either RS1 or RS3 but report significant transmission disequilibrium with the intronic microsatellite. They note moderate linkage disequilibrium between the intronic and the promoter microsatellites.…”
mentioning
confidence: 75%
“…The paper by Yirmiya et al in this issue of Molecular Psychiatry is the third report to test for an association between variations in one of these microsatellites and autism, which is fundamentally a deficit in social behavior. [5][6][7] Kim et al 5 found 17 alleles of RS1, one of which showed increased transmission in a familybased study of 115 autism trios. Wassink et al 6 found significant disequilibrium with both RS1 and RS3 but only in cases without language deficits.…”
mentioning
confidence: 99%